Una mirada desde el Derecho de Familia y Sucesorio, a propósito del derecho de habitación del cónyuge supérstite o si fuere el caso del sobreviviente de la unión de hecho - Aguilar Llanos, Benjamín (Pontificia Universidad Católica del Perú, 2015)
This article focuses on the family estate and the natural fact as death does not end the legal relationships that have led to the heritage that formed the family heritage, this transcends the subject. Therefore, the law regulates the transfer of the rights goods and obligations of the deceased in favor of the person that are his successors. In conclusion, death generates legal consequences.

El presente artículo versa sobre el patrimonio familiar y como un hecho natural como la muerte no culmina las relaciones jurídicas que han dado lugar al patrimonio que formó, sino que ésta trasciende al sujeto, y por ello el Derecho regula la transmisión de los bienes derechos y obligaciones de la persona fallecida a favor de los que resulten sus sucesores. Es decir, la muerte genera consecuencias jurídicas.
A view from Family Law and Inheritance Law, concerning the right of residence of the surviving spouse or survivor is the case of the cohabitation
Keywords: Family; Death; Inheritance Law; Cohabitation; Family Heritage; Familia; Muerte; Derecho Sucesorio; Unión de Hecho; Patrimonio Familiar; https://purl.org/pe-repo/ocde/ford#5.05.00